EVALUASI DAN SIMULASI PENATAAN SIMPANG AHMAD YANI â€“ KPP PRATAMA PONTIANAK - Waskito, Wahyu Putra; Akhmadali, -; Suyono, Rudi Sugiono (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
Congestion usually occurs at the intersection, especially when the intersection is adjacent to the center of the crowd, due to conflicts of movement that occur between vehicles coming from each leg intersection. One intersection with a high level of traffic jam is the intersection of Tax Services Office Pratama Pontianak. The evaluation and simulation of the Arrangement of Intersection Ahmad Yani was done with PKJI evaluation and VISSIM simulation. The purpose of the authors in this study is to determine the reliability of VISSIM for to be applied in the analysis of transportation problems in Indonesia as well as comparing the queue length analysis results using the evaluation results of Indonesia Road Capacity Guidance. Parameter Evaluation of intersection, among others, intersection capacity (C), degree of saturation (DJ), queue length, vehicle stop, delay, and Service Level Index (ITP). The output of the VISSIM simulation is queue length (QLen), Delay, Stop Vehicle (QStop), and Service Level Index (LOS). The results of the two methods above will be compared so that the results obtained close to the actual intersection. After obtained the evaluation and simulation on the existing condition of the intersection it will be planned improvements on the existing condition so that the performance of KPP Pratama Pontianak will be better than the existing condition.Â Keywords: Signalized Intersection, PKJI, VISSIM, Queue Length